Analisis Kinerja Karyawan Ditinjau Dari Keterampilan, Komitmen Organisasi, Kepuasan Kerja Dan Motivasi Karyawan CV. Dimas Jadi Jaya - Mulkan Ritonga; Rahma Muti'ah; Khairil Anshari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This research aims to analyze employee performance in terms of skills, organizational commitment, job satisfaction and employee motivation. This research is quantitative descriptive research using primary data collected through distributing questionnaires online to respondents. Research shows that skills have a positive and significant influence on an employee's resume performance. The calculated t1 value is 2.207 > t table is 1.677 and the significance is 0.033 < 0.05. Organizational commitment has a positive and significant influence on employee performance with a calculated t2 value of 2.607 > t table of 1.677 and a significance of 0.013 < 0.05. Job satisfaction has a positive and significant influence on employee performance with a calculated t3 value of 2.350 > ttable of 1.677 and a significance of 0.023 < 0.05. Motivation has a positive and significant effect on employee performance with a calculated t4 value of 3.659 > t table of 1.677 and a significance of 0.001 < 0.05. Meanwhile, skills, organizational commitment, job satisfaction and motivation have a positive and significant influence on employee performance with an Fcount value of 98.969 while Ftable is 3.19, so Ftable < Fcount, with a significance level of 0.000 > 0.05, at a confidence level of 95% , or alpha 5%.